2005
DOI: 10.1128/jvi.79.16.10278-10288.2005
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Dengue Virus Helicase/Nucleoside Triphosphatase Catalytic Domain at a Resolution of 2.4 Å

Abstract: Dengue fever is an important emerging public health concern, with several million viral infections occurring annually, for which no effective therapy currently exists. The NS3 protein from Dengue virus is a multifunctional protein of 69 kDa, endowed with protease, helicase, and nucleoside 5-triphosphatase (NTPase) activities. Thus, NS3 plays an important role in viral replication and represents a very interesting target for the development of specific antiviral inhibitors. We present the structure of an enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
237
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 200 publications
(253 citation statements)
references
References 48 publications
12
237
4
Order By: Relevance
“…ATPase Activity of DENV4 NS2B 18 NS3 and Mutants-The ATPase activity of DENV4 NS2B 18 NS3 carrying the introduced mutations was measured using the Malachite green assay as reported previously (6). Initially, we determined the activities of wild type DENV4 NS2B 18 NS3 and its helicase domain (residues 172-618), and we found that the helicase domain was only about 30% as active as the full-length protein (the catalytic efficiency, k cat /K m , for NS2B 18 NS3 was taken as 100%).…”
Section: Overall Structural Features Of Ns2bmentioning
confidence: 99%
See 4 more Smart Citations
“…ATPase Activity of DENV4 NS2B 18 NS3 and Mutants-The ATPase activity of DENV4 NS2B 18 NS3 carrying the introduced mutations was measured using the Malachite green assay as reported previously (6). Initially, we determined the activities of wild type DENV4 NS2B 18 NS3 and its helicase domain (residues 172-618), and we found that the helicase domain was only about 30% as active as the full-length protein (the catalytic efficiency, k cat /K m , for NS2B 18 NS3 was taken as 100%).…”
Section: Overall Structural Features Of Ns2bmentioning
confidence: 99%
“…The NS3 protein (618 amino acids in DENV4) contains a serine-protease domain at its N terminus (whose activity requires the formation of a noncovalent complex with the central 40-residue hydrophilic segment of the membrane-bound NS2B protein cofactor) and an ATP-driven helicase and RNA triphosphatase at its C-terminal end. Atomic structures for the active NS3 protease domain (NS2B 47 NS3pro) (2)(3)(4), the ATPase/helicase domain (NS3hel) (5)(6)(7)(8)(9), and the full-length NS3 molecule fused to 18 residues of the NS2B cofactor (NS2B 18 NS3) (10) have been reported and reviewed (11). Together, these structures provide an explanation for the lack of protease activity and solubility observed for NS3pro domains expressed in Escherichia coli (6,12,13).…”
mentioning
confidence: 99%
See 3 more Smart Citations